ASSESSMENT OF EMOTIONAL INTELLIGENCE IN MEDICAL FACULTY AT POONCH MEDICAL COLLEGE (PMC), AZAD JAMMU AND KASHMIR(AJK) - Akram, Zareena; Ahsan Sethi; Aabish Mehreen; Marium Sohail (Journal of University Medical & Dental College, 2021)
ABSTRACT: BACKGROUND & OBJECTIVE: There has been limited understanding of role of emotional intelligence in education and also limited understanding of emotional intelligence levels in teaching and clinical practice. The aim of the current study is to investigate the level of emotional intelligence in medical teachers and see whether emotional intelligence differs in male/female and senior/junior faculty. METHODOLOGY: A cross sectional survey was conducted at Poonch Medical College (PMC), Rawalakot, AJK for 2 months i.e. July to August 2018. Faculty (n=117) from basic pay scale-17 to 21, of basic and clinical sciences departments were included in study after informed consent. Data were collected using “Leadership Toolkit Emotional Intelligence Questionnaire.” Descriptive and inferential statistics were calculated to measure the level of emotional intelligence in faculty members and to quantify variations across gender and position. RESULTS: The response rate in this study was (92.3%) 108/117. There were 56 (51.9%) female and 52 (48.1%) male respondents. Majority of the faculty members 69 (63.9%) were junior level teachers whereas 39 (36.1%) were senior level faculty. The overall mean emotional intelligence was 178.4 ± 21.4, which did not vary across male, and females, or level positions. Self-awareness, was found higher in females (39.9 versus 38.2), however this difference was statistically insignificant (p-value, 0.12). The mean score in managing emotions were also slightly higher in females (33.1 versus 32.5). CONCLUSION: The medical faculty at PMC, AJK has a reasonably high level of emotional intelligence. There was no difference in the overall emotional intelligence levels across gender and position.